Circadian gene variants influence sleep and the sleep electroencephalogram in humans. (27th May 2016) - Chang, Anne-Marie; Bjonnes, Andrew C.; Aeschbach, Daniel; Buxton, Orfeu M.; Gooley, Joshua J.; Anderson, Clare; Van Reen, Eliza; Cain, Sean W.; Czeisler, Charles A.; Duffy, Jeanne F.; Lockley, Steven W.; Shea, Steven A.; et al.
ABSTRACT: The sleep electroencephalogram (EEG) is highly heritable in humans and yet little is known about the genetic basis of inter-individual differences in sleep architecture. The aim of this study was to identify associations between candidate circadian gene variants and the polysomnogram, recorded under highly controlled laboratory conditions during a baseline, overnight, 8 h sleep opportunity. A candidate gene approach was employed to analyze single-nucleotide polymorphisms from five circadian-related genes in a two-phase analysis of 84 healthy young adults (28 F; 23.21 ± 2.97 years) of European ancestry. A common variant in Period2 ( PER2 ) was associated with 20 min less slow-wave sleep (SWS) in carriers of the minor allele than in noncarriers, representing a 22% reduction in SWS duration. Moreover, spectral analysis in a subset of participants ( n = 37) showed the same PER2 polymorphism was associated with reduced EEG power density in the low delta range (0.25–1.0 Hz) during non-REM sleep and lower slow-wave activity (0.75–4.5 Hz) in the early part of the sleep episode. These results indicate the involvement of PER2 in the homeostatic process of sleep. Additionally, a rare variant in Melatonin Receptor 1B was associated with longer REM sleep latency, with minor allele carriers exhibiting an average of 65 min (87%) longer latency from sleep onset to REM sleep, compared to noncarriers. These findings suggest that circadian-related genes can modulate sleep architecture and the sleep EEG, including specific parameters previously implicated in the homeostatic regulation of sleep.